2014
DOI: 10.1097/prs.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Amifostine Reduces Radiation-Induced Complications in a Murine Model of Expander-Based Breast Reconstruction

Abstract: Background Immediate expander-based breast reconstruction after mastectomy is a prevalent option for many women with breast cancer. When coupled with adjuvant radiation, however, radiation-induced skin and soft tissue injury diminish the success of this reconstructive technique. We hypothesize that prophylactic administration of the cytoprotectant Amifostine will reduce soft tissue complications from irradiation, aiding expander-based reconstruction for women battling this disease. Methods Sprague Dawley rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…At present, Androstenediol, OrbeShield ™ , BIO 300, CBLB502, HemaMax ™ and Ex-RAD are some potential radioprotectors which are under Investigational New Drug (IND) status, but require further investigation to be approved by the US Food and Drug Administration (FDA). Although a number of potential drug candidates have been shown to be radioprotective in animal models, most cause significant side effects and are still under pre-clinical or clinical evaluation [ 2 , 11 , 24 , 27 30 ]. For example, Amifostine is FDA-approved to treat xerostomia (dryness of mouth) after head and neck radiotherapy, but it commonly is accompanied with side effects such as nausea, vomiting, chills, fever, dizziness, hypotension and skin rashes [ 27 , 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, Androstenediol, OrbeShield ™ , BIO 300, CBLB502, HemaMax ™ and Ex-RAD are some potential radioprotectors which are under Investigational New Drug (IND) status, but require further investigation to be approved by the US Food and Drug Administration (FDA). Although a number of potential drug candidates have been shown to be radioprotective in animal models, most cause significant side effects and are still under pre-clinical or clinical evaluation [ 2 , 11 , 24 , 27 30 ]. For example, Amifostine is FDA-approved to treat xerostomia (dryness of mouth) after head and neck radiotherapy, but it commonly is accompanied with side effects such as nausea, vomiting, chills, fever, dizziness, hypotension and skin rashes [ 27 , 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of potential drug candidates have been shown to be radioprotective in animal models, most cause significant side effects and are still under pre-clinical or clinical evaluation [ 2 , 11 , 24 , 27 30 ]. For example, Amifostine is FDA-approved to treat xerostomia (dryness of mouth) after head and neck radiotherapy, but it commonly is accompanied with side effects such as nausea, vomiting, chills, fever, dizziness, hypotension and skin rashes [ 27 , 31 34 ]. NEUPOGEN ® (filgrastim) and NEULASTA ® (pegfilgrastim), recently approved by the FDA to treat acute hematopoietic syndrome and neutropenia, respectively, also cause side effects such as bone pain and pain in extremities coupled with other risks such as fatal splenic rupture, acute respiratory distress syndrome, fatal sickle cell crisis, serious allergic reactions, and glomerulonephritis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of amifostine on different radiation types and doses in acute period were studied in recent literature, but there are no study evaluating effects of amifostine on bacterial overgrowth and translocation after acute radiation enteritis [12][13][14] . In our study, the effects of amifostine on both bacterial translocation and bacterial overgrowth in colonic flora after acute radiation enteritis were evaluated in a rat model.…”
mentioning
confidence: 99%
“…Amifostine is a common used radioprotector drug, approved by the United States Food and Drug Administration (FDA). At present, amifostine is mainly used in reducing the side effects induced by radiation therapy in the patients with malignant tumors [ 27 ]. In an in vivo study, Merter et al found that amifostine could attenuate ischemia/reperfusion injury of monkey kidneys by increasing intracellular GSH level [ 28 ].…”
Section: Discussionmentioning
confidence: 99%